Género e historia en Francia: los usos de un término y de una categoría de análisis - Thébaud, Françoise (Cuadernos de Historia Contemporánea, 2006)
What does gender history mean? After investigating the recent emergency of this term in History as well as in Human Sciences in France, this article explains spaces. It describes seven possible uses of the analysis category, and proposes, of course, through an historiographic thought, an scope of recent investigation in this country, concerning women history and gender history.
Keywords: Women History; Gender History; Masculinities History; Sciences History; Historiography